Method for dynamically measuring cerebral oxygen metabolism rate - SHAN YI; QIN LANG; LU JIE; SHU SU; LI QIONGGE; ZHANG MIAO; YIN YAYAN (2020)
The invention discloses a method for dynamically measuring cerebral oxygen metabolism rate. According to the method, a perfusion multiecho asymmetric spin echo technology are adopted, namely, a multiecho signal acquisition mode formed by alternately switching a layer selection inversion mark and a non-layer selection inversion mark is adopted, oxygen extraction fraction (OEF) and cerebral blood flow (CBF) weighted images are synchronously obtained in a mode of adding/subtracting layer selection signals and non-layer selection signals, and measurement of dynamic change of the cerebral metabolicrate of oxygen (CMO2) is finally realized by combining Fick's law. According to the invention, a series of problems caused by gas calibration required by calibrating a blood oxygen level dependent (BOLD) method are fundamentally solved, so that the comfort level of a subject is greatly improved, the applicable population is enlarged, and complexity of operation and measurement cost are greatly reduced. Furthermore, resea